Regulation Improvement of Right to Education Policy for Street Children in Padang City - Aurora Virgonia Niswar; Rozidateno Putri Hanida; Roni Ekha Putera (Sawwa: Jurnal Studi Gender, 2020)
The fulfillment policy of the right to education for street children has been included in some policies in Padang City. However, it still hasn't been able to solve the problem. Hence, policy improvements are as impressive as research topics. The propose of this research is to describe and analyze the implementation process of education rights fulfillment for street children in Padang city. This research was conducted using qualitative research methods and descriptive design by employing library research and field research. The data were collected through interviews and documentation. The results of this research show that the policy needs improvement because there have been obstacles during the impleÂmentation of the policy, which make the policy not function optimally.